2016
DOI: 10.1159/000441801
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of the Implant of a Periurethral Constrictor for Stress Urinary Incontinence Following Radical Prostatectomy

Abstract: Objectives: To assess morbidity, effectiveness and quality of life (QoL) of implant of Silimed periurethral constrictor (PC) in a consecutive series of patients who had stress urinary incontinence following radical prostatectomy. Material and Methods: A prospective non-randomized study designed on patients who underwent implant of Silimed PC. Primary end point was postoperative morbidity and secondary end points were effectiveness of implant and QoL. We performed a sub-analysis of men who received previous rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Relatively many studies described the use of TEG and ROTEM in patients with PFDs. However, the vast majority of these studies consists of case reports involving patients undergoing surgical procedures 136 137 138 139 140 141 142 143 144 145 or during peripartum care. 146 147 148 149 150 151 152…”
Section: Results Of the Point-of-care Tests In Patients With Heredita...mentioning
confidence: 99%
“…Relatively many studies described the use of TEG and ROTEM in patients with PFDs. However, the vast majority of these studies consists of case reports involving patients undergoing surgical procedures 136 137 138 139 140 141 142 143 144 145 or during peripartum care. 146 147 148 149 150 151 152…”
Section: Results Of the Point-of-care Tests In Patients With Heredita...mentioning
confidence: 99%
“…Nonetheless, this device is plagued by high complication rates such as the need to add more fluid in the port to increase the occlusive static pressure of the cuff, urethral erosion, device infection and device malfunction with fluid loss caused by needle perforations in the valve. Recent publication found that Silimed device is not safe with high risk of urethral erosion especially in PPI cohort and that detailed counselling is mandatory when considering the implant in adult patients (73). …”
Section: Methodsmentioning
confidence: 99%
“…For hydraulically controlled AUS, the most classic device is the AMS 800. Due to its frequent complications in clinical use, such as urethral atrophy and mechanical failure, several such devices have followed, such as the Zephyr ZSI 375, 23,24 FlowSecure, 25,26 Adjustable continence therapy, 27,28 BR-SL-AS-904, 29 Periurethral constrictor, 30,31 and VICTO/VICTO+. 32,33 For electromechanically controllable AUS, the devices in the research phase are currently Tape mechanical occlusive device, 34 German artificial sphincter system, 35,36 and Closed Loop Control AUS.…”
Section: Of Ausmentioning
confidence: 99%